Characterizing Adiabaticity in Quantum Many‐Body Systems at Finite Temperature. Issue 7 (19th May 2020) - Skelt, Amy H.; D'Amico, Irene
Abstract: The quantum adiabatic theorem is fundamental to time‐dependent quantum systems, but being able to characterize quantitatively an adiabatic evolution in many‐body systems can be a challenge. This work demonstrates that the use of appropriate state and particle‐density metrics is a viable method to quantitatively determine the degree of adiabaticity in the dynamic of a quantum many‐body system. The method applies also to systems at finite temperature, which is important for quantum technologies and quantum thermodynamics related protocols. The importance of accounting for memory effects is discussed via comparison to results obtained by extending the quantum adiabatic criterion to finite temperatures: it is shown that this may produce false readings being quasi‐Markovian by construction. As the proposed method makes it possible to characterize the degree of adiabatic evolution by tracking only the system local particle densities, it is potentially applicable to both theoretical calculations of very large many‐body systems and to experiments. Abstract : Adiabatic evolutions are vital in quantum physics, but not well understood in many‐body systems at finite temperature. Characterizing adiabaticity using distance measures is shown to be successful for these cases. Importantly, not only quantum state distances (Bures and trace), but also a density distance (a more accessible quantity) can be solely used. An adapted quantum adiabatic criterion is also discussed.